Profesor Bogdan Walczak – lingwista kompletny - Pihan-Kijasowa, Alicja (Slavia Occidentalis, 2013)
Bogdan Walczak, full professor, doctor habilitatus and one of the most distinguished students of Professor Władysław Kuraszkiewicz. Since his graduation from the Polish Faculty of Adam Mickiewicz University in 1965, he developed his career at the Poznań university where he was awarded his doctor and doctor habilitatus degrees. At the behest of the University Council of the Faculty of Polish and Classical Philology he was appointed professor. Bogdan Walczak made his academic debut in 1964. Since that time, he has published over a thousand research and popular science works on various linguistic sub-disciplines, with special emphasis placed on linguistics related to the Polish and Slavic languages. The history of the general Polish language and its regional variations have been at the centre of his research. On the other hand, he has devoted a large part of his work to contemporary Polish, the culture of the Polish language and the cultural heritage enshrined in the Polish language, glottodidactics, onomastics, social linguistics and methodology of linguistic research. Professor Bogdan Walczak is also a valued academic teacher and organizer of research activities. He has received many awards, including the Order of Polonia Restituta and the Medal of the Commission of National Education for his remarkable research and academic achievements and for his organizational work, which has been of such importance to his alma mater. In 2012, when he retired, he was granted the esteemed title of senior professor of Adam Mickiewicz University in Poznań.